Reformulasi Kebijakan SKCK sebagai Penjaminan Hak Non-Diskriminasi dan Akses Kerja Mantan Narapidana - Edward Benedictus Roring (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Police Record Certificate (SKCK) policy as one of the requirements in the labor recruitment process often becomes an obstacle for former convicts to obtain employment. In fact, the right to work is part of human rights (HAM) that should be guaranteed for every individual, including those who have completed their sentence. This study analyzes the impact of the SKCK policy on employment opportunities for former convicts and how its elimination can be a progressive step in realizing human rights equality. This study uses a normative legal approach by examining related regulations, human rights principles, and comparative studies with other countries that have implemented inclusive policies for former convicts in the world of work. The results of the study show that the SKCK policy in job recruitment has the potential to discriminate against former convicts and strengthen social stigma, thus hindering their reintegration process into society. The elimination or at least reform of the SKCK policy to be more inclusive is expected to open up fairer access to employment, strengthen social rehabilitation, and reduce the rate of recidivism. Therefore, changes in regulations and policies are needed that better support the fulfillment of the rights of former convicts to obtain equal employment opportunities.